Isolation and Characterization of a Bacteriocin with Anti-MRSA Activity from Bacillus sp. Strain WASM9-25M - Aunpad, Ratchaneewan; Pipatsatitpong, Duangnate (Journal of Basic and Applied Pharmacology, 2014)
The infection with methicillin resistant Staphylococcus aureus or MRSA has become a serious problem worldwide. The use of a bacteriocin as an alternative compound to overcome this problem is promising. The partially purified bacteriocin or PPB obtained from strain WASM9-25M showed anti-MRSA activity. The PPB was heat stable up to 100°C for 30 min and active within the pH range of 3-9. The inactivation after treatment with all proteolytic enzymes (trypsin, a-chymotrypsin and proteinase K) reveals its antimicrobial peptides. Therefore, this isolated strain WASM9-25M can be regarded as a bacteriocin producing bacteria. It was identified as Bacillus sp. by the 16S rRNA gene sequence. Tris-Tricine SDS-PAGE analysis revealed that bacteriocin from strain WASM9-25M had an apparent molecular weight of 3.14 kDa. PCR analysis showed the presence of iturin A, lichenysin synthetase C and bacillomycin D. The bioactive peptide from Bacillus sp. strain WASM9-25M has a potential for use as an alternative antibacterial agent for the treatment of infection with MRSA in the future.